Textual linking tools for Zaki Naguib Mahmoud, the book of Jannat Al-Obeit as a model - Naeem Amouri Joma Hamidi Hasoni ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
Text scholars show that linking is the consistency between the vocabulary and the sentences that make up the text, and this coordination comes through linguistic means that connect the components of the text, these linguistic means achieved compatibility in both the structural and semantic types. Syntactic consistency is achieved by linguistic means such as deletion, substitution, and conjuncture, and the study was divided into three sections: “In The First Topic we dealt with the definition of the author and the book, and The Second Topic contained a simple vision of linking tools, while The Third Topic“ An applied study on linking tools. Then we concluded the research with some of the findings of the research, the effect of these tools on linking text units to each other from two sides: The first: formality; Where it included verifying the connection between the sentences on the formal level of the text. The second: semantic, which shows the clarification of the linking relationship between the sentences, which led to the understanding of the textual meaning in general. Research methodology is descriptive-analytical.